Tsantan Sumtang Restored Right Ventricular Function in Chronic Hypoxia-Induced Pulmonary Hypertension Rats - Yang, Zhanting; Sun, Haixia; Su, Shanshan; Nan, Xingmei; Li, Ke; Jin, Xueqin; Jin, Guoen; Li, Zhanqiang; Lu, Dianxiang (Frontiers in Pharmacology, 2021)
Background: Tsantan Sumtang originated from Four Tantra, which consisted of Choerospondias axillaris (Roxb.) B.L.Burtt & A.W.Hill, Santalum album L., and Myristica fragrans Houtt. The three herbs are in ratio 1:1:1. This medication is widely used for cardiovascular diseases. Aims: The purpose of this study was to explore the effect of Tsantan Sumtang on RV function in hypoxia induced pulmonary hypertension (HPH) rats and investigate the underlying mechanism. Methods: Sixty male Sprague-Dawley (SD) rats were divided into control, hypoxia, and hypoxia + Tsantan Sumtang (1.0 g•kg-1•d-1, 1.25 g•kg-1•d-1, 1.5 g•kg-1•d-1) groups. Chronic hypoxia was induced by putting the rats inside a hypobaric chamber for four weeks and adjusting the inner pressure and oxygen content to match an altitude of 4500 m. Echocardiography was used to assess RV function and RV-PA coupling. The physiological parameters of the animals were also evaluated. Morphological characteristics of RV were assessed by H&E staining and TEM. Masson's trichrome staining, immunohistochemical staining, western blotting, and TUNEL assay were used to assess fibrosis and apoptosis levels. The antioxidant and anti-apoptosis properties of Tsantan Sumtang were also evaluated. The effect of Tsantan Sumtang on ROCK signaling pathway were evaluated using real-time quantitative PCR and western blotting. Results: We established an HPH rat model as indicated by the significant increases in physiological parameters of the rats. Tsantan Sumtang showed a significant cardiac-protective function and an improved effect on RV-PA coupling. Moreover, Tsantan Sumtang treatment inhibited fibrosis and alleviated apoptosis and oxidative stress in RV. In terms of mechanism, Tsantan Sumtang reduced the expression of ROCK (ROCK1, ROCK2) in RV, inhibited cardiac remodeling-related transcription factors: NFATc3, P-STAT3 and regulated apoptosis-related proteins. Conclusion: Tsantan Sumtang was able to restore RV function, improve RV-PA coupling, recover hemodynamic and hematological indexes, and protect RV against structural maladaptive remodeling in the HPH rats. These findings demonstrated that Tsantan Sumtang protects the function of RV in HPH rats. The antioxidant and anti-apoptosis properties of Tsantan Sumtang may be responsible for inhibiting the ROCK signaling pathway.